Migrations in the Mediterranean IMISCOE Regional Reader - Zapata-Barrero, Ricard; Awad, Ibrahim (IMISCOE Research Series, 2024)
This open access Regional Reader describes population movement circulating within the Mediterranean area, for any reason or from any region, be them European, African, Asian or originating from any of the Mediterranean shores. It showcases a plurality of approaches to and applications of Mediterranean migration, contributing to a regional approach to migration studies, thereby defending this regional approach by scaling Mediterranean migration issues. This book covers a large set of questions related Mediterranean migrations to the migration research agenda, such as: market and economy, politics and policies, super-diversity and intersectionality, media, society, welfare and the environment through five main parts: Geo-political Mediterranean Relations, Governance, Policies and Politics, Mobility drivers and Agency, Cities, History and Social Transformations, and Economy and Labour Markets. This Regional Reader provides an interesting read to scholars, researchers, but also policy makers and civil society organizations' high representatives, international foundations and institutions interested in linking the Mediterranean and migration.